The neglected members of the family: non-BRCA mutations in the Fanconi anemia/BRCA pathway and reproduction. (19th January 2022) - Vanni, Valeria Stella; Campo, Giovanni; Cioffi, Raffaella; Papaleo, Enrico; Salonia, Andrea; Viganò, Paola; Lambertini, Matteo; Candiani, Massimo; Meirow, Dror; Orvieto, Raoul
Abstract: BACKGROUND: BReast CAncer ( BRCA ) genes are extensively studied in the context of fertility and reproductive aging. BRCA proteins are part of the DNA repair Fanconi anemia (FA)/BRCA pathway, in which more than 20 proteins are implicated. According to which gene is mutated and which interactions are lost owing to the mutation, carriers and patients with monoallelic or biallelic FA/BRCA mutations exhibit very different phenotypes, from overt FA to cancer predisposition or no pathological implications. The effect of the so far neglected non-BRCA FA mutations on fertility also deserves consideration. OBJECTIVE AND RATIONALE: As improved treatments allow a longer life expectancy in patients with biallelic FA mutations and overt FA, infertility is emerging as a predominant feature. We thus reviewed the mechanisms for such a manifestation, as well as whether they also occur in monoallelic carriers of FA non-BRCA mutations. SEARCH METHODS: Electronic databases PUBMED, EMBASE and CENTRAL were searched using the following term: 'fanconi' OR 'FANC' OR 'AND' 'fertility' OR 'pregnancy' OR 'ovarian reserve' OR 'spermatogenesis' OR 'hypogonadism'. All pertinent reports in the English-language literature were retrieved until May 2021 and the reference lists were systematically searched in order to identify any potential additional studies. OUTCOMES: Biallelic FA mutations causing overt FA disease are associated with premature ovarian insufficiency (POI) occurring in the fourth decade in women and with primary non-obstructive azoospermia (NOA) in men. Hypogonadism in FA patients seems mainly associated with a defect in primordial germ cell proliferation in fetal life. In recent small, exploratory whole-exome sequencing studies, biallelic clinically occult mutations in the FA complementation group A ( Fanca ) and M ( Fancm ) genes were found in otherwise healthy patients with isolated NOA or POI, and also monoallelic carrier status for a loss-of-function mutation in Fanca has been implicated as a possible cause for POI. In those patients with known monoallelic FA mutations undergoing pre-implantation genetic testing, poor assisted reproduction outcomes are reported. However, the mechanisms underlying the repeated failures and the high miscarriage rates observed are not fully known. WIDER IMPLICATIONS: The so far 'neglected' members of the FA/BRCA family will likely emerge as a relevant focus of investigation in the genetics of reproduction. Several (rather than a single) non-BRCA genes might be implicated. State-of-the-art methods, such as whole-genome/exome sequencing, and further exploratory studies are required to understand the prevalence and mechanisms for occult FA mutations in infertility and recurrent miscarriage.